CFD Simulation of Photovoltaic Thermal (PV/T) Cooling System with Various Channel Geometries - I Gede Febri Bala Antara; Made Sucipta; Ketut Astawa; I Ketut Gede Wirawan; Made Sukrawa (Journal of Heat and Mass Transfer Research)
Photovoltaic/thermal (PV/T) is a solution for solar energy conversion devices to increase their efficiency. One of the challenges of PV/T is maintaining the temperature at optimal working conditions. Various studies have been conducted to improve PV/T performance, one of which is through the design of thermal collectors on PV/T. In this study, Computational Fluid Dynamics (CFD) simulations were conducted using four different types of channels: circular, hexagonal, semi-circular, and square. The channels were made with the same tube cross-sectional area and mass flow rate of 0.0016 m2 and 0.0096 kg/s, respectively. The simulation results show that the circular channel numerically gives the lowest PV cell temperature, 317.95 K, with an electrical efficiency of 14.70% and a thermal efficiency of 44.18%. This is because the water velocity in the circular channel can be faster than the other channels.  The circular channel has a thinner boundary layer, so the velocity is maximized, and the heat transfer rate increases.